Relationship Marketing Dalam Membangun Loyalitas Melalui Kepuasan Pelanggan Paket Data - Setiyawan, Setiyawan (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Abstract. Relationship marketing is an effort to build a good constructive relationship with selected costumers (loyality) in order to achieve long-term marketing success through costumer satisfaction data packet. The results of this study showed that relationship marketing had a direct effect of satisfactory (0.745). Relationship marketing had also directly affect of loyality (0.237) and satisfactory had a direct effect with loyality (0.405). The results about indirect effect of relationship marketing with loyality through satisfactory is (0.745 x 0405) = 0.302, because beta coefficient value 0.234 < 0.302, so satisfactory variable could mediate relationship marketing with loyality. Key word : Relationship marketing, loyality, costumer satisfaction